Education, socio-economic status and age-related macular degeneration in Asians: the Singapore Malay Eye Study. Issue 10 (29th July 2008) - Cackett, P; Tay, W T; Aung, T; Wang, J J; Shankar, A; Saw, S M; Mitchell, P; Wong, T Y
Abstract : Background/aims: Low socio-economic status is increasingly being identified as a risk marker for chronic diseases, but few studies have investigated the link between socio-economic factors and age-related macular degeneration (AMD). The present study aimed to assess the association between socio-economic status and the prevalence of AMD. Methods: A population-based cross-sectional study of 3280 (78.7% response rate) Malay adults aged 40–80 years residing in 15 south-western districts of Singapore. AMD was graded from retinal photographs at a central reading centre using the modified Wisconsin AMD scale. Early and late AMD signs were graded from retinal photographs following the Wisconsin grading system. Socio-economic status including education, housing type and income were determined from a detailed interview. Results: Of the participants, 3265 had photographs of sufficient quality for grading of AMD. Early AMD was present in 168 (5.1%) and late AMD in 21 (0.6%). After adjusting for age, gender, smoking, hypertension, diabetes and body mass index, participants with lower educational levels were significantly more likely to have early AMD (multivariate OR 2.2, 95% CI 1.2 to 4.0). This association was stronger in persons who had never smoked (multivariate OR 3.6, 95% confidence CI 1.4 to 9.4). However, no association with housing type or income was seen. Conclusions: Low educational level is associated with a higher prevalence of early AMD signs in our Asian population, independent of age, cardiovascular risk factors and cigarette smoking.